2022
DOI: 10.3390/math10132356
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Impact on the Unsteady Separated Stagnation-Point Flow of Hybrid Nanofluid with Viscous Dissipation and Joule Heating

Abstract: The behaviour of magnetic impact on the unsteady separated stagnation-point flow of hybrid nanofluid with the influence of viscous dissipation and Joule heating is investigated numerically in this study. A new mathematical hybrid nanofluid model is developed, and similarity solutions are obtained in the form of ordinary differential equations (ODEs). The bvp4c approach in MATLAB is used to determine the reduced ODEs’ estimated solutions. The influence of various physical parameters is scrutinised. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The unsteady separated stagnation-point flow of hybrid nanofluid with viscous dissipation and Joule heating is investigated numerically in this examined by Amira Zainal et al [46]. Zainal et al [47] have investigated viscous dissipation and MHD hybrid nanofluid flow towards an exponentially stretching/shrinking surface.…”
Section: Introductionmentioning
confidence: 99%
“…The unsteady separated stagnation-point flow of hybrid nanofluid with viscous dissipation and Joule heating is investigated numerically in this examined by Amira Zainal et al [46]. Zainal et al [47] have investigated viscous dissipation and MHD hybrid nanofluid flow towards an exponentially stretching/shrinking surface.…”
Section: Introductionmentioning
confidence: 99%
“…Their research revealed the presence of a dual solution for the shrinking region within a particular range, and the impact of Ec widened the range of solutions. Recently, Zainal et al [54] sought to conduct research on hybrid nanofluids toward stagnation-point flow for the unsteady flow problem while considering the influence of Joule heating together with viscous dissipation. The examination of boundary layers and heat transport in Joule heating has been a fascinating topic addressed by researchers over the years, and it has produced several noteworthy mentions [55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…The stability between the two different solutions is an important consideration that must be considered. It provides a technique for determining which solution is stable, as other scholars [27,42,54] have already done in their outstanding study on stability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This research shows hybrid nanofluids relating to their theoretical study, thermophysical properties, solar radiation, thermal applications, and numerical estimation including machine learning. he available literature indicates that hybrid nanofluids are more effective than nanofluids in enhancing the thermal performance of base fluids as described in [16,17,18,19,20,21]. This is because the thermal performance of nanofluids is limited in relation to their specific thermal and chemical properties.…”
Section: Introductionmentioning
confidence: 99%